Assessment of Client Satisfaction in Out Patient Departments of Sub-District Hospitals in South India - T C, Akshay kumar; Devagappanavar, Dr. Gulappa (Jour Med Resh and Health Sci, 2023)
Background: Patient satisfaction is a universal concept. Patient satisfaction is one of the well-established methods for assessing the success of health-care services. Nowadays, more emphasis is placed on patient satisfaction because it is an important factor in evaluating hospital services. One of the most important aspects of hospital administration is the Out-Patient Department (OPD) Services. Client satisfaction reflects the gap between the expected service and the client’s experience of the services. Because patient satisfaction is regarded as a healthcare outcome and predictor of treatment utilization and adherence to care and support, assessing patient satisfaction is critical. A recent study from a tertiary level government hospital in India found that patient satisfaction ranged between 70% and 80%. Satisfaction with service delivery is increasingly being used to assess health-care system performance. Satisfaction is reflected in the distribution. Objectives: To assess the level of satisfaction among clients attending outpatient departments receiving health services at Gadag district Sub-District hospitals. To compare the levels of satisfaction among patients across departments. To identify the reasons of satisfaction and dissatisfaction in order to assist administrators in improving the situation. Materials and methods: A hospital-based cross-sectional study was conducted to assess client satisfaction in outpatient departments of Gadag District sub-district hospitals. By obtaining permission from the District Health Office and the appropriate officer in the health force. The convenient sampling technique was used to select study participants who are both convenient and cooperative. A standard questionnaire was used to collect data, information about socio-demographic details, and the level of Patient Satisfaction. An interview schedule was created in order to identify the reasons satisfaction and dissatisfaction. The data were entered into excel sheet and the results were expressed in satisfaction scale. Results: The study included 400 clients (Patients) ranging in age from 35 to 45 years. The majority of Clients (32.8 percent) in our study were illiterate. Almost all (90.8 percent) of the clients were from rural areas. The vast majority of patients (90.5 percent) were Hindus, with 24.3 percent being unskilled laborers. Currently, BPL cards are held by 98.8 percent of clients. The current study found that the overall average level of patient satisfaction was 57.85 percent. In sub-district hospitals, satisfaction levels were found to be 67.9 percent in Nargundi taluk hospital, 58.1 percent in Mundargi taluk hospital, 48.3 percent in Shirahatti taluk hospital, and 57.1 percent in Ron taluk hospital. The Ortho department at Nargundi taluk hospital had the highest level of satisfaction (96.6 percent) and the general surgery department had the lowest level of satisfaction (43.3 percent). Interdepartmental comparisons at Mundargi taluk hospital revealed that the general surgery department (75 percent) had the highest level of satisfaction and the ortho department had the lowest level of satisfaction (38.3 percent). The Ortho department (66.6 percent) had the highest level of satisfaction in Shirahatti taluk hospital, while the OBG department had the lowest level of satisfaction (28.3 percent). Comparisons at Ron Taluk Hospital revealed that the general surgery department (68.3 percent) had the highest level of satisfaction and the Ortho department had the lowest level of satisfaction (40 percent). Good consultation (42.8 percent) and free treatment were given as reasons for satisfaction by nearly all clients (54.0 percent). Unsanitary restrooms (25.3 percent) and longer wait times were given as reasons for dissatisfaction by half of the clients (24.8 percent). Conclusion: The current study discovered that Patient Satisfaction is a simple, easy, and cost-effective method for evaluating overall hospital services and has aided in discovering that patients were satisfied with doctor behavior, but the issue lies with the availability of basic amenities and dissatisfaction was found to be more concerning drinking water, cleanliness in the toilets, and the wards. However, if the survey findings are translated into actions to improve the quality of health care, they can be quite useful. Keywords: Client satisfaction; outpatient department; sub-district hospital; Patient Satisfaction; health services; sub-district hospitals